Short-term effects of wildfire on soil arthropods in a semi-arid grassland on the Loess Plateau - Yang, Xi; Liu, Ren-Tao; Shao, Ming-An; Wei, Xiao-Rong; Li, Tong-Chuan; Chen, Ming-Yu; Li, Zhi-Yong; Dai, Yun-Chao; Gan, Miao (Frontiers in Microbiology, 2022)
ABSTRACT Fires lead to dramatic shifts in ecosystems and have a large impact on the biota. Soil organisms, especially soil fauna, are often used as indicators of environmental change. At present, minimal attention has been paid to using soil fauna as an indicator of environmental change after a fire. Here, a field survey of burnt herbaceous vegetation in semi-arid areas was conducted to determine the response of soil arthropods to fire and their short–term recovery after fire. Overall, the abundance and biomass of soil arthropods was more sensitive to fire than the number of groups. The number of soil arthropod groups, especially the dominant groups (mites and springtails), was not significantly affected by wildfires. At the unburned site, soil arthropod abundance showed significant seasonal shifts that may be related to the vegetation properties, temperature, and precipitation caused by seasonal changes. In contrast, soil arthropods at the burnt sites showed a delayed recovery and had only reached 56–82%, 17–54%, and 91–190% of the biomass in the unburnt forest at the third, sixth, and ninth months after the burning event. Our findings of soil arthropod abundance changes in the present study suggest that fire-induced changes in soil and vegetation properties (e.g. AN, LT and VC) were crucial factors for the changes in soil arthropod abundance in this semi-arid grassland. We conclude that fire disturbance reduces the seasonal sensitivity of soil arthropods by altering their habitat. This study furthers our understanding of wildfire impact recovery by documenting the short-term temporal dynamics of soil arthropods.